A DFT‐based method for estimating interharmonics in wind power generation. Issue 5 (26th May 2022) - Monteiro, Henrique L. M.; Camponogara, Ândrei; Ribeiro, Moisés V.; Duque, Carlos A.; Poor, H. Vincent
Abstract: This paper introduces a discrete Fourier transform (DFT)‐based method for estimating the amplitudes and frequencies of interharmonics, which arise from the interaction between wind power generators and electric power systems. This method exploits the synergy of choosing signal enhancement, mains frequency estimation, and re‐sampling techniques. Consequently, it accomplishes a cost‐effective estimation process. The performance results show that signal enhancement and re‐sampling techniques are necessary to establish suitable conditions for performing amplitude and frequency estimation. Furthermore, numerical results show that the proposed method, relying on low‐cost digital signal processing techniques, offers competitive performance and significant computational complexity reduction compared to a previous DFT‐based method.